Successful management of dystocia due to ankylosed foetal monster through fetotomy in a buffalo - Singh, Vipin; Patel, Akhil; Yadav, Chhote Lal; Gupta, Rishi Kumar; Saxena , Atul (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Dystocia is the most common sequelae of foetal monstrosities in bovines. Fetal anomalies and monstrosities of various kind causing dystocia in cattle (Arthur et al., 1989; Patel et al., 2015) and buffaloes (Kumaresan et al., 2003 and Shukla et al., 2006) have been documented. The present paper describes about management of dystocia due to ankylosed foetal monster through fetotomy in a Murrah buffalo.